In patients with diabetic foot, improved left ventricular functions are detected by strain echocardiography after the diabetic foot treatment: A cross-sectional study. Issue 38 (September 2019) - Demirtas, Derya; Kucukosmanoglu, Mehmet
Abstract : Abstract: Diabetic foot is a macrovascular complication of diabetes mellitus (DM). In the literature, the relationship between diabetic foot and another macrovascular complication of DM is not clear. The aim of this study was to determine the current left ventricular (LV) systolic function in patients with diabetic foot and to investigate the effect of diabetic foot treatment on LV systolic functions. In this study, 54 patients with diabetic foot and 22 patients without diabetic foot were included. Routine anamnesis, physical examination, echocardiography, and laboratory examinations were performed. In addition, LV global longitudinal strain (LV-GLS) was measured by strain echocardiography technique. LV ejection fraction (LV-EF) and LV-GLS measurements were repeated with echocardiography at the 3rd month of diabetic foot treatment. The incidence of cardiovascular risk factors such as smoking, hypertension, and coronary artery disease was found to be higher in patients with diabetic foot. ( P  < .05 for each one). Similarly, in patients with diabetic foot, glucose, Hemoglobin A1c, neutrophil, sedimentation, urea, creatinine, potassium, uric acid, alanine aminotransferase, aspartate aminotransferase, C-reactive protein, and brain natriuretic protein were higher; high-density lipoprotein cholesterol level was found to be significantly lower. LV wall thicknesses and diameters were higher and LV-EF was lower in patients with diabetic foot ( P  < .05 each one). LV-GLS values were significantly lower in patients with diabetic foot ( P  < .05). Although no significant change was found in the LV-EF value at the 3rd-month follow-up echocardiography (48.6% ± 7.0% vs 48.5% ± 5.9% and P  = .747), it was detected that LV-GLS values (17.3 ± 2.1 vs 18.4 ± 2.3) were significantly increased ( P  < .001). LV systolic function was significantly affected in patients with diabetic foot. This may be related to the increased frequency of cardiovascular risk factors in these patients. However, the significant improvement in LV-GLS values after the diabetic foot treatment showed that diabetic foot itself was an important cause of LV systolic dysfunction.